2000
DOI: 10.1099/00221287-146-8-2059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aberrant virulence of Gibberella zeae following transformation-mediated complementation of a trichothecene-deficient (Tri5) mutant

Abstract: Gibberella zeae causes wheat ear blight and produces trichothecene toxins in infected grain. In previous studies, trichothecene production in this fungus was disabled by specific disruption of the trichodiene synthase gene (Tri5) and was restored by two methods : gene reversion and transformation-mediated mutant complementation. In previous field tests of wheat ear blight, trichothecene-nonproducing mutants were less virulent than the wild-type progenitor strain from which they were derived. Trichothecene-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Although some MAT deletion strains and other transformants were less virulent than the wild-type strain from which they were derived, the reduced virulence of these transformants was linked to the source of protoplasts and not to the transforming DNA. Thus, it is likely that procedures used for protoplast production and transformation reduced virulence by causing alterations at loci other than the targeted gene, a phenomenon previously observed in transformationmediated gene disruption in G. zeae (11).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although some MAT deletion strains and other transformants were less virulent than the wild-type strain from which they were derived, the reduced virulence of these transformants was linked to the source of protoplasts and not to the transforming DNA. Thus, it is likely that procedures used for protoplast production and transformation reduced virulence by causing alterations at loci other than the targeted gene, a phenomenon previously observed in transformationmediated gene disruption in G. zeae (11).…”
Section: Discussionmentioning
confidence: 94%
“…Virulence tests were conducted on cultivar Wheaton as previously described (11). Heads were inoculated by injecting a drop of macroconidium suspension containing approximately 10 3 macroconidia into one floret of a central spikelet of each head.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, our data demonstrate that indirect mutagenesis and transformation events alter central carbon metabolism in H. jecorina in similar manners. Desjardins et al (6) also observed that Gibberella zeae can undergo spontaneous or transformation-induced mutations that significantly altered its virulence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genes related to well conserved signal transduction pathways (Hou et al, 2002;Jenczmionka et al, 2003;Jenczmionka and Schafer, 2005;Urban et al, 2003;Yu et al, 2008), a number of pathogenicity genes with diverse biological or biochemical functions have been characterized (Han et al, 2007;Lee et al, 2005;Lu et al, 2003;Seong et al, 2005Seong et al, , 2006Shim et al, 2006). The first pathogenicity factor most thoroughly characterized by molecular studies in F. graminearum is the trichodiene synthase gene TRI5 (Desjardins et al, 2000;Proctor et al, 1995). Although trichothecene mycotoxins are not necessary for the initial infection, they are important for the spread of the fungus within colonized spikes (Bai et al, 2002;Desjardins et al, 2000;Harris et al, 1999;Proctor et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…The first pathogenicity factor most thoroughly characterized by molecular studies in F. graminearum is the trichodiene synthase gene TRI5 (Desjardins et al, 2000;Proctor et al, 1995). Although trichothecene mycotoxins are not necessary for the initial infection, they are important for the spread of the fungus within colonized spikes (Bai et al, 2002;Desjardins et al, 2000;Harris et al, 1999;Proctor et al, 1995). In the past decade, the trichothecene biosynthetic gene cluster and biosynthesis pathway have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%